In vitro antibacterial and in silico docking studies of two Schiff bases on Staphylococcus aureus and its target proteins - Ragi K; Joby Thomas Kakkassery; Vinod P. Raphael; Reeja Johnson; Vidhya Thomas K (SpringerOpen, 2021)
Abstract Background Schiff base compounds have extensive applications in various fields such as analytical, inorganic, organic, and biological fields. They have excellent pharmacology application prospects in the modern era and are widely used in the pharmaceutical industry. In the present work in vitro antibacterial and in silico docking studies of two Schiff base compounds 2,2'-(5,5-dimethylcyclohexane-1,3-diylidene)bis(azan-1-yl-1-ylidene)diphenol (DmChDp) and N,N'-(5,5-dimethylcyclohexane-1,3-diylidene)dianiline (DmChDa) were carried out against the bacterial strain Staphylococcus aureus and its target proteins. Results The tests proved that the ligands have potential antibacterial activity. In the computational analysis, the drug-like properties of the compounds were first pre-filtered using the Lipinski rule of five. Then, molecular docking study was conducted using the AutoDock 4.2 program, to establish the mechanism by which the molecules inhibit the growth of S. aureus. For this purpose, 6 different target proteins (PDB ID: 1T2P, 3U2D, 2W9S, 1N67, 2ZCO, and 4H8E) of S. aureus were selected. Both the Schiff bases showed a good binding affinity with the target protein dihydrofolate reductase enzyme (PDB ID: 2W9S) but in different sites. Maximum binding energies of about − 10.3 and − 10.2 kcal/mol were observed when DmChDp and DmChDa were docked with 2W9S. Conclusion Schiff base compounds DmChDp and DmChDa have appreciable growth-inhibitory power against S. aureus, which can be attributed to the deactivation of the enzyme, dihydrofolate reductase.